DIVERSION IN COURT (Case Studies in Karanganyar District Court) - Anita Zulfiani (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Children are the future generation. But in society, children can make mistakes and errors, and sometimes those errors can be categorized as a criminal offense, thus making a Children in conflict with the law. Child in conflict with the law should undergo the legal process.  But children have different psychological maturity from adults, so Children should not be treated the same as adults when they in conflict with the law. Concern for children as one of human resources, which is a potential successor to the nation's future, bringing awareness that children need special attention when dealing with the law. It encourages the establishment of rules on the treatment of children who commit criminal acts and must deal with the law. Regulations on handling children who commit criminal acts is Act No. 3 of 1997 on Juvenile Court. This rule is considered not giving enough protection to the child in conflict with the law, then Act Number 11 of 2012 on Juvenile Justice System enforced. In these rules there is a relatively new thing, the rules regarding Diversion. Diversion procedure resembles mediation, conducted before the trial phase in the Court. If the diversion succeed,  the case will be terminated and did not proceed to trial. Diversion process aimed at realizing the restorative justice, where all the parties involved (victims, children, and the community) and jointly to solve the problems and create an obligation to make things better in seeking solutions to repair, reconciliation and reassurance, which not by retaliation1. To achieve the restorative justice on the Juvenile Justice System, it is necessary to succeed the diversion process, at the level of investigation, prosecution, and examination in the courts, for the child in conflict with the law. Therefore, the author will attempt to find the answer of the questions: What is diversion? Why diversion should be pursued? How to succeed the diversion process? So that at the end of this writing, we can find conclusion about the things that can support the success of the diversion process.